Nested Saturation Function Control of a Magnetic Levitation System - Octavio Gutiérrez-Frías; Norma Lozada-Castillo; J. Alejandro Aguirre-Anaya; Diego A. Flores-Hernández (Complexity)
The trajectory tracking task of a magnetic levitation system connected to a beam mechanism is solved by means of a nested saturation control with a feedforward term. The flatness property of the system allows to use the nested saturation control technique and the feedforward control to stabilize the output tracking error around the equilibrium. The closed-loop error dynamics is proven to be locally exponentially stable. Numerical simulations prove the effectiveness of the proposal.